Hydrogen production using solar energy and injection into a solid oxide fuel cell for CO2 emission reduction; Thermoeconomic assessment and tri-objective optimization. (March 2022) - Cao, Yan; Dhahad, Hayder A.; ABo-Khalil, Ahmed G.; Sharma, Kamal; Hussein Mohammed, Adil; Anqi, Ali E.; El-Shafay, A.S.
Highlights: Biomass fueled solid oxide fuel cell is integrated with solar-based hydrogen production. Two configurations are proposed depending on how the hydrogen is injected into the system. Tri-objective optimization is performed based on efficiency, cost and CO2 emission. Hydrogen injection significantly decreases the CO2 emission and biomass consumption. Despite of increased investment costs, the levelized cost of electricity decreases. Abstract: The integrated biomass gasification-Solid Oxide Fuel Cell (SOFC) technology combines benefits of renewable and hydrogen energy-based systems. In this work, this system is incorporated with solar-powered hydrogen production and injection into the SOFC to provide higher hydrogen concentration in fuel mixture of the SOFC. Proton Exchange Membrane Electrolyzer (PEME) is employed for hydrogen production, meanwhile its required power is generated by solar Photovoltaic-Thermal (PVT) panels. The proposed system with hydrogen injection is modeled and its performance is evaluated and compared with that of conventional integrated biomass gasification-SOFC system in terms of thermodynamics, environmental impacts and economics. In thermoeconomic assessment, the environmental damage costs resulted from CO2 emissions as the primary greenhouse gas is taken into account. Via conducting a parametric study the major design variables are determined and then, a tri-objective optimization is performed based on levelized product cost, CO2 emissions, and exergy efficiency. It is found that, the proposed system has significantly lower CO2 emissions compared to the conventional system. Under optimal operation, the proposed system with hydrogen injection yields lower CO2 emission by 12.9% and higher output power by 8.7% at the expense of 6.3 percentage points reduction in exergy efficiency, compared to the conventional system. Despite the additional costs associated with the solar PVT panels and electrolyzer, the proposed system yields almost the same product cost compared to the conventional system. This point can be accounted as an important and remarkable advantage for the proposed system in this work.